Efficient implicit methods for wellbore shear failure analysis during drilling and production in coalbeds. (July 2022) - Zhong, Ruizhi; Mitchell, Travis; Johnson, Raymond; Leonardi, Christopher
Abstract: Wellbore instability is an important consideration during both drilling and production of hydrocarbon reservoirs. The optimal well trajectory must be determined during the design phase to avoid wellbore shear failures. This study makes two fundamental contributions towards improving contemporary wellbore shear models. For the first time, the analytical wellbore shear models are formulated implicitly to significantly improve the computational efficiency and obtainable accuracy. The stability problem is resolved with the bisection method and an optimisation algorithm, where Powell's method and the Nelder-Mead method have been implemented here. The second contribution is to account for the depletion of various formations, especially coal, in the stability models. Three stress models, namely those of Gray, Shi and Durucan, and Cui and Bustin, were used to develop stress paths for a depleted coal reservoir. The results were quantified via the maximum allowable pressure (MAP), which indicates the wellbore pressure required to avoid wellbore failure and thus guide corresponding operational decisions. The results of this work show that implicit methods significantly improve computational efficiency over the conventional iterative method used in the literature and industry. In particular, it was found that Powell's method saves greater than 95% of the computation time for sandstone and coal case studies, respectively. In terms of stability during depletion, a higher depletion pressure resulted in an increased MAP. For a drilling application, this means that a greater overbalance pressure is required. While in a production application, a lower maximum drawdown pressure would be expected. The Gray model indicates the largest impact on stability prediction for depleted coals, and the Cui and Bustin model is the most conservative among the three stress models. The proposed numerical framework provides an efficient tool to determine the optimal well trajectory for different formations (e.g. coal, clastic rock) experiencing depletion before or after drilling.